PRELIMINARY STUDY ON ENVIRONMENTAL AWARENESS OF STUDENTS WITH THE IMPLEMENTATION OF ENVIRONMENTAL EDUCATION IN SCHOOLS IN INDIA - Shimray, C.V.; Sasidharan, Rashmi (SCHOOL SCIENCE, 2014)
Environmental education (EE) in India is implemented by infusing various environmental concerns through different subject areas in all stages of school education. In addition, there is a separate project-based syllabus compulsory for all students at the higher secondary stage. In spite of these efforts, it was felt that students in general had different notions about what constitutes ‘environment’. Correct understanding of term environment is inevitable to achieving the objectives of EE. Besides, EE also envisages students to be familiar with the local environmental problems and provide the necessary skill to address such problems. Hence this study was undertaken as a preliminary research to find out students' basic understanding about the environment, their local environmental problems and their outlook towards such problems. The study revealed some basic issues for example, in their understanding about the term ‘environment’ and in their inability to connect their school curriculum and the environment outside their classroom.